CYBERBULLYING IN YOUTUBE’S COMMENTS ON “TRIBUN MEDAN TV CHANNEL” - Sitinjak, Vivi Novalia; Panjaitan, Devi Tania; Silitonga, Bahagia Halomoan; Yoehadi, Vincent (Universitas Hasanuddin, 2023)
Cyberbullying is defined as bullying, threatening, and even harming a person using electronic communication which has been happening lately and can be seen in our daily life. The purpose of this study is to identify the types of cyberbullying used by the commenter and understand how they bully others in their comments. Things that might happen such as mental down, death, etc. This study applies a qualitative descriptive method. In order to analyze the data, researchers employ an interactive analysis model that Miles and Huberman (1992:23) proposed. The result of this study finds 15 comments containing instances of cyberbullying. The findings are three types of cyberbullying are present on the